Early Civilization and the American Modern - Miller, Eva (UCL Press, 2024)
In the late nineteenth and early twentieth century, a particular story about the United States’ role in the long history of world civilization was constructed in public spaces, through public art and popular histories. This narrative posited that civilization and its benefits – science, law, writing, art and architecture – began in Egypt and Mesopotamia before passing ever further westward, towards a triumphant culmination on the American continent.